Why Is This Man Laughing?. Issue 2 (3rd May 2016) - Hamelman, Steve
Abstract : There is a good deal of humor, from dry and ironical to raunchy and tasteless, in the music and live monologues of Lou Reed, both as a member of the Velvet Underground and as a solo artist. To examine Reed's wide-ranging humor in terms of the three major categories comprising the philosophy of humor (Superiority theory, Incongruity theory, and Relief theory) is to appreciate the nuances of a rock humorist who could at one point be heard laughing at the end of a song about heroin's destructiveness and at another point delivering a scathing but hilarious attack on well-known rock journalists who annoyed him. As this analysis demonstrates, the diversity of tone, subject matter, and manner of delivery of Reed's humor reflects an artist who satisfied, in terms defined as much by courage as by literary skill, the three classic divisions of humor, suggesting that despite his reputation for writing dark and often cynical songs about taboo topics, Lou Reed enjoyed hearing the sound of laughter, sometimes his own, when he gave free expression to his comic genius.